REGULASI DIRI MAHASISWA BERPRESTASI - Husna, Aftina Nurul; Hidayati, Frieda N.R.; Ariati, Jati (Jurnal Psikologi, 2014)
AbstractSelf-regulation is considered as one of the success key for students. Self-regulation process involves one’s activities to produce thoughts, feelings, and actions, to plan and continuously to adapt in order to achieve the targeted goals. This study aims to describe the experiences of best students in self-regulating themselves, particularly in improving their achievement as a student as endorsed by the university. Two students who won the Best Students Competition held by a university had participated in this study. A qualitative phenomenological approach was used in this study. Data was collected using interview and subsequently were analyzed using the transcendental phenomenological method. The study focused on finding meaning and understanding the selfregulatory process of students in pursuing their academic achievement. The findings showed that self-regulation was defined as having an integrated thoughts, feelings, and actions, continuously, and targeted in pursuing the achievement. Self-regulation was a process in guiding self towards a holistic person, academically (to be a best student), socially (to be a good child as well as a good sister), and existentially (to be a useful person).